The association between lymphocyte-to-monocyte ratio and all-cause mortality in obese hypertensive patients with diabetes and without diabetes: results from the cohort study of NHANES 2001–2018 - Wang, Lixia; Gao, Jie; Liu, Bing; Fu, Youliang; Yao, Zhihui; Guo, Shanshan; Song, Ziwei; Zhang, Zhaoyuan; He, Jiaojiao; Wang, Congxia; Ma, Weidong; Wu, Feng (Frontiers in Endocrinology, 2024)
Objective Obesity, hypertension and diabetes are high prevalent that are often associated with poor outcomes. They have become major global health concern. Little research has been done on the impact of lymphocyte-to-monocyte ratio (LMR) on outcomes in these patients. Thus, we aimed to explore the association between LMR and all-cause mortality in obese hypertensive patients with diabetes and without diabetes.The researchers analyzed data from the National Health and Nutrition Examination Survey (2001Survey ( -2018)), which included 4,706 participants. Kaplan-Meier analysis was employed to compare survival rate between different groups. Multivariate Cox proportional hazards regression models with trend tests and restricted cubic splines (RCS) analysis and were used to investigate the relationship between the LMR and all-cause mortality. Subgroup analysis was performed to assess whether there was an interaction between the variables.The study included a total of 4706 participants with obese hypertension (48.78% male), of whom 960 cases (20.40%) died during follow-up (median follow-up of 90 months). Kaplan-Meier curves suggested a remarkable decrease in all-cause mortality with increasing LMR value in patiens with diabetes and non-diabetes (P for log-rank test < 0.001). Moreover, multivariable Cox models demonstrated that the risk of mortality was considerably higher in the lowest quartile of the LMR and no linear trend was observed (P > 0.05). Furthermore, the RCS analysis indicated a non-linear decline in the risk of death as LMR values increased (P for nonlinearity < 0.001).Increased LMR is independently related with reduced all-cause mortality in patients with obese hypertension, regardless of whether they have combined diabetes.